2022
DOI: 10.3390/md20020119
|View full text |Cite
|
Sign up to set email alerts
|

Possible Functional Roles of Patellamides in the Ascidian-Prochloron Symbiosis

Abstract: Patellamides are highly bioactive compounds found along with other cyanobactins in the symbiosis between didemnid ascidians and the enigmatic cyanobacterium Prochloron. The biosynthetic pathway of patellamide synthesis is well understood, the relevant operons have been identified in the Prochloron genome and genes involved in patellamide synthesis are among the most highly transcribed cyanobacterial genes in hospite. However, a more detailed study of the in vivo dynamics of patellamides and their function in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 131 publications
(227 reference statements)
0
8
0
Order By: Relevance
“…Such biochemical insights can be applied to the rationally engineered creation of large libraries of synthetic compounds for lead compound identification [ 42 ]. The ecological roles of these symbiont-derived cyanobactins have been proposed, including metal ion sequestration and/or transport, chemical defense and catalysis and/or transport of substrates [ 43 ]. Along with P. didemni , the tunicate host also houses a novel symbiotic α-proteobacterium, Ca.…”
Section: Chemical Ecology-driven Discovery Of Marine Medicinesmentioning
confidence: 99%
“…Such biochemical insights can be applied to the rationally engineered creation of large libraries of synthetic compounds for lead compound identification [ 42 ]. The ecological roles of these symbiont-derived cyanobactins have been proposed, including metal ion sequestration and/or transport, chemical defense and catalysis and/or transport of substrates [ 43 ]. Along with P. didemni , the tunicate host also houses a novel symbiotic α-proteobacterium, Ca.…”
Section: Chemical Ecology-driven Discovery Of Marine Medicinesmentioning
confidence: 99%
“…The true biological function of these interesting macrocycles and their metal complexes, however, is not yet known. [5,6] A recent study has shown, that fluorescencelabeled patellamide analogues bind copper(II) ions in vivo, [4] and this, together with the known complex stabilities (specifically Cu II vs. Zn II ) and the observed accumulation of Cu II in ascidians (approx. 10 4 -fold vs. the surrounding seawater), supports the general assumption that the copper(II) coordination chemistry of patellamides is of biological relevance.…”
Section: Introductionmentioning
confidence: 97%
“…The complexes have shown the ability to catalyze a wide range of reactions of potential metabolic relevance, such as carbonic anhydrase, phosphatase, β‐lactamase and glucosidase. The true biological function of these interesting macrocycles and their metal complexes, however, is not yet known [5,6] . A recent study has shown, that fluorescence‐labeled patellamide analogues bind copper(II) ions in vivo, [4] and this, together with the known complex stabilities (specifically Cu II vs. Zn II ) and the observed accumulation of Cu II in ascidians (approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of key metabolites of the prokaryote Prochloron didemni, a photosynthetic symbiont of the sea squirt Lissoclinum patella, cyclic pseudo-octapeptides such as ascidiacyclamide, patellamides AÀ G and ulicyclamide are expressed via the ribosomal RiPP pathway and are known to be of medicinal interest. [1][2][3][4][5][6][7] These natural products and especially their Cu II chemistry have gained the interest of coordination chemists, [1,3] also because the Cu II concentration in their ascidian host is about two orders of magnitude higher than in the surrounding sea water. [8] The biosynthesis of the azole/azoline-based cyclic peptides is known and biochemical in vitro methods for their production have been developed.…”
Section: Introductionmentioning
confidence: 99%